2019
DOI: 10.1021/acsami.9b04625
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cellular Colonization of Porous Polyurethane Scaffolds via the Control of Pore Interconnection Size and Nanoscale Surface Modifications

Abstract: Full-scale cell penetration within porous scaffolds is required to obtain functional connective tissue components in tissue engineering applications. For this aim, we produced porous polyurethane structures with well-controlled pore and interconnection sizes. Although the influence of the pore size on cellular behavior is widely studied, we focused on the impact of the size of the interconnections on the colonization by NIH 3T3 fibroblasts and Wharton's jelly-derived mesenchymal stem cells (WJMSCs). To render … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…[26] and references therein. In particular, experimental results were reported [27] to generate porous polyurethane by a sphere templating method as an attempt to control the interconnection size for a given bead diameter (bead sintering). We are not aware of any experimental setup able to produce well-dened (geometrically) polymeric structures having closed and open pores of dierent ratios.…”
Section: Discussionmentioning
confidence: 99%
“…[26] and references therein. In particular, experimental results were reported [27] to generate porous polyurethane by a sphere templating method as an attempt to control the interconnection size for a given bead diameter (bead sintering). We are not aware of any experimental setup able to produce well-dened (geometrically) polymeric structures having closed and open pores of dierent ratios.…”
Section: Discussionmentioning
confidence: 99%
“…The final structure is an accurate reproduction of the initial template whose pore size and shape are fixed by the size and shape of the sacrificial particles which are typically salt [ 33 ] ( Figure 1 f) due to its high solubility in aqueous media and preventing the use of organic solvents. However, other sacrificial agents can be found in the literature, as for example, polymers [ 34 ]. This simple approach provides the control on the pore size by fixing the size of the sacrificial agent which can be selected according to the needs, which are usually ranging from tens to hundreds of microns.…”
Section: Overview Of the Techniques Used For Fabrication Of Porousmentioning
confidence: 99%
“…Despite the fact that this parameter appears to be important regarding cell migration, the relationship between interconnection diameter and cell behavior is poorly documented in the literature compared to pore size and porosity [ 148 ]. One reason is that the generation of scaffolds with controlled pore size and interconnectivity remains challenging and is not possible for most of the fabrication processes, although some approaches such as sphere templating and 3D printing allow it [ 34 , 149 ].…”
Section: Review Of the Influence Of The Scaffold Architecture On Cmentioning
confidence: 99%
“…Hence the stents that are beneficial to bone tissue regeneration can be selected based on pore size. Studies have shown that scaffolds with a pore size of 100-200 µm have obvious osteogenic effects in vitro (Brennan et al, 2019), and stents with a pore size of about 133 µm are conducive to the production of extracellular matrix in vitro (Lutzweiler et al, 2019). However, studies by Oh et al (2007) have shown that in in vivo experiments scaffolds of 290-310 µm are more suitable for the formation of new bones.…”
Section: Scanning Electron Microscope (Sem) Analysismentioning
confidence: 99%